Study on consumer preferences towards vegetables - Diana Maria Necula; Daniela Nicoleta Bădan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Vegetables play an important role in human nutrition, as they have a high content of nutrients. In the last five years, there has been a tendency to increase the consumption of vegetables among Romanians, this being attributed to the increase of the living standard, but also to the reorientation of the population towards a healthier diet. The present study aims to determine the profile of vegetable consumers by highlighting their attitude and preferences. The research method used in the research paper was the questionnaire administered to a representative sample of 403 respondents. The study identified aspects related to the frequency of buying vegetables, but also the factors that can influence the decision to buy vegetables, such as their condition (frozen, fresh, processed vegetables) and their origin. The identified aspects were related to several socio-professional indicators (sex, age, place of residence, level of education, income) that can define the consumer profile.
Keywords: D11; E21; Q11; Q13; 330; profile; consumption; preferences